Limited role of continental arc in crustal growth: Insights from zircon U-Pb ages and Lu-Hf isotopes of late Paleozoic granitoid plutons from the northern North China Craton - Jing Ran; Hao Wang; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Yu-Sheng Zhu (Lithos, 2026)

Macroscopic crack ratio as a structural surrogate linking linear filtration and nonlinear expression in sludge dewatering - Yi-Wen Yuan; Hao-Ran Chen; Zhi-Hao Liu; Shi-Yu Ren; Chang-Ji Huang; Raymond Jianxiong Zeng; Hou-Feng Wang (Process Safety and Environmental Protection, 2026)

Impact of waste biomass binders on the pelletizing, combustion, and engineering feasibility of sludge–coal slime co-pelletized fuel - Hao-Ran Chen; Yi-Wen Yuan; Zhi-Hao Liu; Chang-Ji Huang; Shi-YuS Ren; Hou-Feng Wang; Raymond Jianxiong Zeng (Environmental Research, 2026)

Synthesis of hierarchically micro-mesoporous carbon nanospheres: Molecular insight into the role of hexamethylenetetramine on the pore architecture - Ran Yuan; Shuxia Yuan; Yu Yang; Chunxiang Lu; Guohua Sun; Shijie Wu; Xiaodan Ren; Hao Cui (Chemical Engineering Journal, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Lipid profile of sheep milk and its impact on taste: a combination study of lipidomics and electronic tongue - Hao Yuan; Zhongshi Zhu; Yuxin Wang; Chang Chen; Haozhan Liu; Ran Li; Liwei Zhang; Yuxuan Song (Food Research International, 2026)

Metal-air fuel cells for phosphorus recovery from wastewater: A critical analysis of principles, progress, and application perspectives - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Yuan Liu (Chemical Engineering Journal, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Photothermal-responsive Au nanorod-silica nanocomposite with on-demand curcumin release for sequential therapy of biofilm infections - Wenhui Jiang; Shunlan Luo; Kehan Du; Kai Yuan; Yuanhua Cong; Xiaoping Zeng; Dawei Wang; Hongyang Zhao; Huinan Suo; Liu Yang; Xiaowen Ou; Hao Jiang; et al. (Chemical Engineering Journal, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A multi-component recycling strategy for photovoltaic waste: Co-recovering silicon and PVDF into Ag–F reinforced Si/C anodes - Yihao Li; Yiqing Chen; Xiaojiao Zhang; Yaoguang Guo; Shuai Chen; Jie Yang; Tie Lin; Haodong Ran; Yang Zhang; Qin Xu; Yanlin Wu; Hao Yuan; et al. (Resources, Conservation and Recycling, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Tensile-compressive hysteresis performance of prestressed CFDST columns for offshore wind turbine structures - Kai-Yuan Jin; Xu-Hong Zhou; Chao Hu; Kang Wang; Yu-Hang Wang; Hao-Ran Xu (Ocean Engineering, 2026)

Bio-based anhydride crosslinked furan-derived vitrimeric epoxy networks with intrinsic flame retardancy, self-healing capacity and recyclability - Tian-Mo Yang; Hao-Xin Niu; Wen-Jie Zheng; Hao-Ran Jiang; Yuan Hu; Xin Wang (Journal of Cleaner Production, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

Latest progress based on doped-TiO2 photocatalysis materials: Fabrication and applications - Xiao-Ni Qi; Ya-Qi Zhu; Hui Yuan; Zi-Xuan Xu; Hao-Ran Guo; Zhen-Liang Li (Journal of Water Process Engineering, 2025)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

Glycosidase inhibitory isoflavones from the seeds of Cullen corylifolium and their structure–activity relationship study - Ying-Xiao Xiao; Yi-Ran Jiang; Wen-Hui Xu; Yuan Gao; Tian-Tian Bei; Hao Xu; Xue-Feng Wu; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Assessing river-blocking risks of ancient landslide in mountainous regions: insights from a slow-moving, high-position reactivated ancient landslide in the Southeast Tibetan Plateau - Xinfu Xing; Changbao Guo; Tanfang Zhu; Peng Xin; Hao Yuan; Yiqiu Yan; Congyan Ran (Bulletin of Engineering Geology and the Environment, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Effects of 1-oleate-2-palmitate-3-linoleate glycerol supplementation on the small intestinal development and gut microbial composition of neonatal mice - Fang Wu; Yaqiong Liu; Ming Zhang; Xinlei Yuan; Tengteng Ji; Yutong Jin; Yixuan Li; Ran Wang; Yanling Hao; Bing Fang (Food Research International, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Behavior of super-sized thin-walled CFDST columns for wind turbine towers subjected to combined loads: Experiment - Kai-Yuan Jin; Yu-Hang Wang; Xu-Hong Zhou; Ran Deng; Chao Hu; Hao Wen (Engineering Structures, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Ionic liquids bonded in mesoporous HAP serve as efficient catalysts for CO2 fixation - Decun Luo; Zhen-Yu Zhang; Hao Yuan; Xi-Yang Yu; Xin Gao; Zhun Hu; Chun-Ran Chang (Chemical Engineering Journal, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Over-expression of miR-3584-5p Represses Nav1.8 Channel Aggravating Neuropathic Pain caused by Chronic Constriction Injury - Ran Yang; Qian-qian Wang; Yuan Feng; Xue-hao Li; Gui-xia Li; Feng-lin She; Xi-jin Zhu; Chun-li Li (Molecular Neurobiology, 2023)

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

Three-dimensional macroporous structure and surface carbon-coating modification of stainless-steel anode boost bioelectrocatalytic performance - Cheng-Yan Liu; Hao-Yi Cheng; Si-Yuan Zhai; Ran Zeng; De-Xin Zhang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

Estimation of quality factors by energy ratio method - Zong-Jun Wang; Si-Yuan Cao; Hao-Ran Zhang; Ying-Ming Qu; Dian Yuan; Jin-Hao Yang; Guan-Ming Shao (Applied Geophysics, 2015)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Analysis of quality factors for Rayleigh channel waves - Xiao-Hui Yang; Si-Yuan Cao; De-Chun Li; Peng-Fei Yu; Hao-Ran Zhang (Applied Geophysics, 2014)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

CLOCK/BMAL1 regulates human nocturnin transcription through binding to the E-box of nocturnin promoter - Ran Li; Jiping Yue; Yu Zhang; Lan Zhou; Wei Hao; Jiangang Yuan; Boqin Qiang; Jian M. Ding; Xiaozhong Peng; Ji-Min Cao (Molecular and Cellular Biochemistry, 2008)